(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the role of innovative technologies in increasing the export potential of local manufacturers. It is argued that the introduction of modern technologies significantly increases the quality, competitiveness and compliance with international standards of products. Also, the improvement of digital technologies, automated production processes and logistics systems is considered as an important factor in expanding export volumes. The article highlights the possibilities of reducing production costs, using resources efficiently and capturing new markets using innovative approaches. In addition, the issues of stimulating innovative development through state support mechanisms and attracting investments are also discussed. As a result, it is concluded that the widespread introduction of innovative technologies is an important condition for increasing the export potential of local manufacturers.